Prognostic Role of Hypoxia-Inducible Factor-2α Tumor Cell Expression in Cancer Patients: A Meta-Analysis - Moreno Roig, Eloy; Yaromina, Ala; Houben, Ruud; Groot, Arjan J.; Dubois, Ludwig; Vooijs, Marc (Frontiers in Oncology, 2018)
Hypoxia-inducible factor-2α (HIF-2α) plays an important role in tumor progression and metastasis. A number of studies have evaluated the correlation between hypoxia-inducible factor-2α (HIF-2α) overexpression and clinical outcome in cancer patients but yielded inconsistent results. To comprehensively and quantitatively summarize the evidence on the capability of HIF-2α to predict the prognosis of cancer patients, a meta-analysis was carried out. Renal cell carcinoma (CC-RCC) was separately analyzed due to an alternative mechanism of regulation. Systematic literature searches were performed in PubMed and Embase databases for relevant original articles until Feb 2018. Forty nine studies with 6,052 patients were included in the present study. The pooled hazard ratios (HRs) with corresponding confidence intervals (CIs) were calculated to assess the prognostic value of HIF-2α protein expression. The meta-analysis revealed strong significant negative associations between HIF-2α expression and five endpoints: overall survival (HR = 1.69, 95% confidence interval (95%CI) 1.39–2.06), disease-free survival (HR = 1.87, 95%CI 1.2–2.92), disease-specific survival (HR = 1.57, 95%CI 1.06–2.34), metastasis-free survival (HR = 2.67, 95%CI 1.32–5.38) and progression-free survival (HR = 2.18, 95%CI 1.25–3.78). No association was observed with locoregional control. Subgroup analyses revealed similar associations in the majority of tumor sites. A positive (but not significant) association between good prognosis and HIF-2α expression was seen for kidney and bladder cancer. This meta-analysis indicated that the HIF-2α may serve as a useful prognostic biomarker in various cancers.